2012
DOI: 10.1016/j.jvs.2011.11.057
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling leads to distinctly more intimal hyperplasia in coronary than in infrainguinal vein grafts

Abstract: Although coronary and infrainguinal bypass surgery uses saphenous veins as conduits, they undergo significantly different remodeling processes in these two anatomic positions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…NH has been well examined in coronary bypass grafts but is different for peripheral surgery in terms of flow patterns, blood pressure and graft length (Westerband et al 2000;Zilla et al 2012). Altered shear stress may even be protective against hyperplasia but did not prevent graft failure in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…NH has been well examined in coronary bypass grafts but is different for peripheral surgery in terms of flow patterns, blood pressure and graft length (Westerband et al 2000;Zilla et al 2012). Altered shear stress may even be protective against hyperplasia but did not prevent graft failure in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our ex vivo system also allows for compensation for the possible influence that different anatomical locations may have on the arterialization of grafted veins, providing a unique platform to explore the different factors that may contribute to modify the grafted vessels. 3,25 Remodeling requires the integrated effects of the fibrinolytic system, MMPs, and their inhibitors. We have shown that elevation of PAI-1 26 is induced by the arterial shear stress and, in contrast to IH, is not markedly influenced by the hemodynamic pressure.…”
Section: Discussionmentioning
confidence: 99%
“…(Takumi et al 2010) While compensatory remodeling of coronary vasculature initially maintains shear stress, (Dolan et al 2012; Huo and Kassab 2012; Samady et al 2011) remodeling-mediated neointimal hyperplasia is conducive to the development of high shear stress in response to reduced vessel lumen diameters. (Zilla et al 2012) The presence of pre-atherosclerotic lesions further engenders disturbed flow downstream to the stenosis, (Varghese and Frankel 2003; Zhang 2009) recruiting monocyte and LDL particles transmigration into the subendothelial layers (Ai et al 2009; Davies et al 1986) as well as promoting atherothrombosis. (Bark Jr and Ku 2010) Using the ApoE knockout mouse model with the constrictive carotid artery collars, Ding et al reported elevated shear stress within the constrictive regions and low shear stress at proximal regions coupled with endothelial disfunction(Ding et al 2010).…”
Section: Discussionmentioning
confidence: 99%